Permissioned Blockchain and Smart Contracts for Halal Supply Chain Traceability in Indonesia - Rafi Farizki; Rani Santika; Vo Hung Cuong (Publikasi Indonesia, 2026)
Assurance of halal integrity along the supply chain carries major economic and religious weight in Indonesia, yet conventional traceability relies on centralized databases and paper certificates that are difficult to verify, easy to tamper with, and fragmented across the many actors between farm and consumer. This study designs and evaluates HalalChain, a permissioned-blockchain and smart-contract traceability framework that records each custody transfer on a shared, tamper-evident ledger and encodes halal certification rules as executable logic. Using a design science methodology, supply-chain actors participate as permissioned nodes on Hyperledger Fabric, bulky documents are stored off chain with only their cryptographic hashes on chain, and consumers verify authenticity by scanning a code; the framework was compared against a centralized-database baseline across throughput and latency, scalability, traceability completeness and time to trace, and security and trust, complemented by a structured expert assessment. The evaluation indicates that the permissioned blockchain strengthens traceability and trust, yielding a more complete, verifiable history, faster tracing, and demonstrated tamper-evidence and access control, while keeping performance within practical bounds through the on-chain/off-chain design. The framework provides a deployable reference architecture linking blockchain traceability to halal certification governance, transferable to other provenance-critical chains. A permissioned blockchain can improve halal traceability and trust at an acceptable performance cost.